Morphological and Molecular Identification of Three Ceriodaphnia Species (Cladocera: Daphniidae) from Australia. (14th December 2014) - Sharma, Pranay
Abstract : Australian Ceriodaphnia (Cladocera: Daphniidae) are examined using morphological attributes and two mitochondrial DNA (COI and 16s) and one nuclear DNA (28s) gene fragments to differentiate the species. The sequence data supports the existence of three species, that is, C. dubia, one reinstated species C. spinata Henry, 1919, and one new species C. sp. 1. Morphological characteristics were also able to accurately separate the three species. Furthermore, genetic analysis of COI sequences from Ceriodaphnia supported three clades. The high degree of correlation between morphological and molecular identification in this study indicates that mitochondrial markers, COI and 16s, are appropriate molecular markers for species discrimination and identification of Ceriodaphnia .